Anaemia and associated factors among older adults in an urban district in China: a large-scale cross-sectional study. Issue 3 (9th March 2022) - Ni, Wenqing; Yuan, Xueli; Sun, Yuanying; Zhang, Hongmin; Zhang, Yan; Xu, Jian
Abstract : Objective: Anaemia leads to poor health outcomes in older adults; however, most current research in China has focused on younger adults. This study aimed to investigate the prevalence of anaemia and its associated factors in older adults in an urban district in China. Design: A cross-sectional study. Setting: An urbanised region, Shenzhen, China. Participants: A total of 121 981 participants aged ≥65 years were recruited at local community health service centres in Shenzhen from January to December 2018. Primary outcomes: The prevalence of anaemia was analysed and potential associated factors were evaluated. Results: The mean haemoglobin level was 136.40±16.66 g/L and the prevalence of anaemia was 15.43%. The prevalences of mild, moderate and severe anaemia were 12.24%, 2.94% and 0.25%, respectively. Anaemia was positively associated with older age, being underweight (adjusted OR (AOR) 2.06, 95% CI 1.93 to 2.20), diabetes (AOR 1.23, 95% CI 1.19 to 1.28) and chronic kidney disease (AOR 1.41, 95% CI 1.36 to 1.46), and inversely with higher education level, current-smoker (AOR 0.84, 95% CI 0.78 to 0.89), non-habitual drinker (AOR 0.86, 95% CI 0.81 to 0.92), habitual drinker (AOR 0.81, 95% CI 0.75 to 0.87), overweight (AOR 0.67, 95% CI 0.64 to 0.70), obesity (AOR 0.57, 95% CI 0.53 to 0.61), central obesity (AOR 0.86, 95% CI 0.82 to 0.89), hypertension (AOR 0.86, 95% CI 0.83 to 0.89) and dyslipidaemia (AOR 0.81, 95% CI 0.78 to 0.84). Conclusion: Anaemia is prevalent among people aged 65 years and older in China. Screening of high-risk populations and treatment of senile anaemia should be a top priority in Shenzhen, and should be listed as important public health intervention measures for implementation.